PSYCHOSPIRITUAL, STRESS, AND COPING STRATEGY OF PULMONARY TUBERCULOSIS PATIENT: A LITERATURE REVIEW - Suhendra Agung Wibowo; Muhammad Amin; Laily Hidayati (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Tuberculosis can cause psychological disorders in a person. Spiritual approaches can be used to improve coping strategies to suppress stress symptoms that arise. Objective: The purpose of this study is to describe the psychospiritual conditions, stress and coping strategies that occur in patients with tuberculosis. Design: The research design uses systematic review based on PRISMA checklist. Data Sources: Using three databases; Scopus, Science Direct and EBSCO. The search was conducted from January to March 2021. The keyword “tuberculosis” OR “pulmonary TB’ OR “psychology” OR “spiritual” OR “stress” OR “coping strategy” was used in this systematic review with journal articles, 2016-2021 publication years and English as searching limitation. Review Methods: JBI Critical Appraisal Tool used to assess the quality of the articles and PRISMA checklist used as a guideline to filter articles. Results: 10 articles were obtained according to the inclusion criteria. The results of the analysis showed 7 articles using a cross sectional design, 2 quasi-experimental, and 1 qualitative study. The number of samples with a cross-sectional design ranged from 45 to 1,342, while articles with a quasi-experimental, qualitative and comparative study design had 32, 15 and 78 patients with pulmonary TB as respondents. Almost all of the psychological conditions in pulmonary TB patients experience stress and coping disorders. The results of the analysis show that spirituality can be used to improve the coping strategies used so as to suppress the stress symptoms that arise. Conclusion: Psychospiritual strategies can be used as a way to improve the coping of TB sufferers and reduce the stress they experience.